Production of leukotriene B4 and prostaglandin E2 by turbot (Scophthalmus maximus) leukocytes - Tafalla, Carolina; Medina, Isabel; Figueras Huerta, Antonio; Novoa, Beatriz (Comparative Biochemistry and Physiology Part B: Biochemistry and Molecular Biology, 1999)
6 páginas, 4 figuras Production of two eicosanoids derived from lipoxygenase and cyclooxygenase activities: leukotriene B4 (LTB4) and prostaglandin E2 (PGE2), respectively, have been simultaneously determined in turbot (Scophthalmus maximus) blood leucocyte and kidney macrophage supernatants by a reverse phase high performance liquid chromatography (HPLC) system coupled with a Diode–Array detector. Levels of LTB4 after calcium ionophore challenge were 4.08 ng ml 1 in blood leukocyte supernatants and 0.25 ng ml 1 in kidney macrophage supernatants. The levels found for PGE2 were 428.23 and 606.67 ng ml 1 in blood leukocytes and kidney macrophage supernatants, respectively. When blood leukocytes were treated with the respective inhibitors for the enzymes implicated on the synthesis of both compounds an inhibition of 90.35% was observed for PGE2 and 76.44% for LTB4. The detection limit of the method was 0.15 ng ml 1 for LTB4 and 50 ng ml 1 for PGE2. This research was supported by grant MAR 96-1775 from the Comision Interministerial de Ciencia y Tecnologia (CICYT, Spain). Peer reviewed